2012
DOI: 10.3389/fimmu.2012.00214
|View full text |Cite
|
Sign up to set email alerts
|

Expression of XCR1 Characterizes the Batf3-Dependent Lineage of Dendritic Cells Capable of Antigen Cross-Presentation

Abstract: Cross-presentation of antigen by dendritic cells (DCs) to CD8+ T cells is a fundamentally important mechanism in the defense against pathogens and tumors. Due to the lack of an appropriate lineage marker, cross-presenting DCs in the mouse are provisionally classified as “Batf3-IRF-8-Id2-dependent DCs” or as “CD8+ DCs” in the spleen, and as “CD103+CD11b− DCs” in the periphery. We have now generated a mAb to XCR1, a chemokine receptor which is specifically expressed on CD8+ DCs and a subpopulation of double nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
195
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(212 citation statements)
references
References 48 publications
16
195
0
1
Order By: Relevance
“…Furthermore, venus was not expressed in CD11c 2 cells, including T, B, and NK cells, granulocytes, and monocytes. These expression patterns are consistent with the previous findings based on the expression pattern of LacZ knocked into the Xcr1 locus or analysis with anti-XCR1 Ab (26,27,30,31 DCs and that functional CD8a + DCs can be tracked in our mutant mice. It is also notable that the XCR1 expression level was unchanged after injection of LPS or poly(I:C) (Fig.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Furthermore, venus was not expressed in CD11c 2 cells, including T, B, and NK cells, granulocytes, and monocytes. These expression patterns are consistent with the previous findings based on the expression pattern of LacZ knocked into the Xcr1 locus or analysis with anti-XCR1 Ab (26,27,30,31 DCs and that functional CD8a + DCs can be tracked in our mutant mice. It is also notable that the XCR1 expression level was unchanged after injection of LPS or poly(I:C) (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…A chemokine receptor, XC chemokine receptor 1 (XCR1), is selectively expressed in splenic CD8a + and peripheral CD103 + DCs but is rare in other DC subsets or lymphocytes (26)(27)(28)(29)(30)(31). Human XCR1 expression is restricted to CD141 + DCs, which correspond to murine splenic CD8a + DCs (27-29, 32, 33).…”
mentioning
confidence: 99%
“…+ CD24 low cells (6,7,27) showed that they were dominated by Ly-6C high monocytes and moDCs. In contrast, 24 h after laser microporation the numbers of LCs, XCR1…”
Section: Cd11bmentioning
confidence: 99%
“…Institutes of Health, Bethesda, MD), and anti-CD40 (FGK) by T. Rolink (University of Basel, Basel, Switzerland). Generation of anti-XCR1 mAb MARX10 (19) and anti-ICOS mAb (MIC-280 (25)) has been described before. The nonagonistic mAb MARX10 (mouse IgG2b, in the recombinant version IgG1) does not block the binding of XCL1 to XCR1.…”
Section: Expression and Purification Of Recombinant Proteinsmentioning
confidence: 99%
“…In the past few years, we and others recognized that the chemokine receptor XCR1 is exclusively expressed on the Batf3-dependent, crosspresenting DC and not elsewhere in the body (17)(18)(19). This highly restricted expression of XCR1 in the mouse is mirrored in the human system, where XCR1 can only be found on DC homologous to the mouse cross-presenting subset (18,20,21).…”
mentioning
confidence: 99%